On the Occasion of the Seventieth Birthday of Professor Jiang Lishang (Journal of Partial Differential Equations, 2006)
Professor Jiang Lishang was chief editor of Journal of Partial Differential Equation for 15 years. He made a great effort in the development of this journal. Through the excellent works of him and his colleagues, this journal is playing a more and more important role in the research on partial differential equations in China.